Receptions of Greek and Roman antiquity in East Asia - Renger, Almut-Barbara,; Fan, Xin (Historian), (Metaforms, 2018)
Receptions of Greek and Roman Antiquity in East Asia is an interdisciplinary, collaborative, and global effort to examine the receptions of the Western Classical tradition in a cross-cultural context. The inclusion of modern East Asia in Classical reception studies not only allows scholars in the field to expand the scope of their scholarly inquiries but will also become a vital step toward transcending the meaning of Greco-Roman tradition into a common legacy for all of human society.